Synthesis of Dipyridylaminoperylenediimide-Metal Complexes and Their Cytotoxicity Studies - José Garcés-Garcés; Marta Redrado; Ángela Sastre-Santos; María Concepción Gimeno; Fernando Fernández-Lázaro (MDPI AG, 2022)
A new family of perylenediimide (PDI) silver and copper complexes has been successfully synthesized by reacting ortho- and bay-substituted (dipyrid-2',2"-ylamino)perylenediimide ligands with metal phosphine fragments. The coordination of the metal center did not reveal a significant effect on the photophysical properties, which are mainly due to the PDI ligands, and in some cases quenching of the luminescence was observed. The antiproliferative effect of the free perylenediimide ligands and the metalloPDI complexes against the cervix cancer cell line HeLa was determined by MTT assay. The free perylenediimide ligands exhibited a moderate cytotoxic activity, but the coordination of silver or copper to the dypyridylamino fragment greatly enhanced the activity, suggesting a synergistic effect between the two fragments. In attempts to elucidate the cellular biodistribution of the PDIs and the complexes, a colocalization experiment using specific dyes for the lysosomes or mitochondria as internal standards revealed a major internalization inside the cell for the metal complexes, as well as a partial mitochondrial localization.